2023
DOI: 10.3390/v15122381
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signature of a Novel Alternanthera Yellow Vein Virus Variant Infecting the Ageratum conyzoides Weed in Oman

Muhammad Shafiq,
Gabrijel Ondrasek,
Abdullah Mohammed Al-Sadi
et al.

Abstract: Alternanthera yellow vein virus (AlYVV), a monopartite begomovirus, has been identified infecting a diverse range of crops and native plants in Pakistan, India, and China. However, distinctive yellow vein symptoms, characteristic of begomovirus infection, were observed on the Ageratum conyzoides weed in Oman, prompting a thorough genomic characterization in this study. The results unveiled a complete genome sequence of 2745 base pairs and an associated betasatellite spanning 1345 base pairs. In addition, Seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recent studies have shown the association of satellite molecules with begomoviruses infecting weeds in diverse regions. Weed Sinapis arvensis is a reservoir of begomoviruses and associated betasatellites in Jordan [ 60 ]; Solanum nigrum is a host of tomato leaf curl Palampur virus and CLCuMB in Pakistan [ 61 ]; Ageratum conyzoides and Amaranthus spinosus are hosts of Ageratum yellow vein China virus and tomato leaf curl Java beta satellite in Indonesia [ 62 ]; and A. conyzoides is a host of Alternanthera yellow vein virus and tomato leaf curl betasatellite in Oman [ 63 ]. Earlier studies have shown the presence of multiple and recombinant betasatellites in weeds Digera arvensis and Sonchus arvensis [ 64 , 65 ].…”
Section: Origin and Evolution Of Satellites Associated With Begomovir...mentioning
confidence: 99%
“…Recent studies have shown the association of satellite molecules with begomoviruses infecting weeds in diverse regions. Weed Sinapis arvensis is a reservoir of begomoviruses and associated betasatellites in Jordan [ 60 ]; Solanum nigrum is a host of tomato leaf curl Palampur virus and CLCuMB in Pakistan [ 61 ]; Ageratum conyzoides and Amaranthus spinosus are hosts of Ageratum yellow vein China virus and tomato leaf curl Java beta satellite in Indonesia [ 62 ]; and A. conyzoides is a host of Alternanthera yellow vein virus and tomato leaf curl betasatellite in Oman [ 63 ]. Earlier studies have shown the presence of multiple and recombinant betasatellites in weeds Digera arvensis and Sonchus arvensis [ 64 , 65 ].…”
Section: Origin and Evolution Of Satellites Associated With Begomovir...mentioning
confidence: 99%